Relasi Makna dalam Bahasa Serawai Dialek ‘AU’ (Sinonim, Antonim, Dan Homonim) di Desa Pasar Pino Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Anggraini, Zelvia; Akbarjono, Ali; Heriadi, Meddyan (Lembaga Riset dan Inovasi Almatani, 2024)
Serawai language is an important cultural heritage for the Serawai tribe, but its use has declined among the younger generation due to the influence of globalization. This study aims to explore and describe the form of synonym, antonym, and homonym meaning relations in the Serawai language dialect